A Systems Approach to International Education: How Administrative Data is Being used to Track the Progress of USAID’s Education Strategy - Asrar, Sadaf (International Journal of Population Data Science, 2018)
While rigorous evaluation of donor funded education interventions are quite common in developing countries, the data collected and analyzed to assess the interventions are not always published. Even when published, the data often lack codebooks and technical documentation, guidance on how to correctly use the data, and most frustratingly only contain meta-information pertaining to the design of the intervention and evaluation in free text in PDF reports. Such practices reduce the overall quality of the data and meta-data making it very difficult to be used for secondary analysis to answer policy relevant questions. To address such challenges, this paper describes the integrated data system developed to securely receive, review, harmonize, ingest, curate, and publish standardized public use Early Grade Reading Assessment data and meta-data to track the progress of the 2011-2015 USAID Education Strategy. The paper discusses the underlying methodological framework for systematically reviewing the data for quality and completeness as well as the approach to profile the design of the intervention and evaluation to assess its rigor using the system. Lastly, the paper illustrates how the meta-data created through the systematic review process combined with the data collected and processed through the system can be used for developing dynamic data products that reduce the technical barriers for such data to be used by a wide range of stakeholders to inform critical policy decisions.